Association Between Smoking and Wound Infection Rates Following Calcaneal Fracture Fixation. Issue 4 (August 2014) - Soni, Ashish; Vollans, Samuel; Malhotra, Karan; Mann, Christopher
Fixation of displaced, intra-articular calcaneal fractures has shown to improve outcome, but wound complications can be devastating for the patient. While smoking remains a factor associated with poor outcome, evidence is still somewhat contradictory. We studied the association of smoking and wound complication after calcaneal fracture fixation. In addition, we evaluated infection rates and association with age of patient, delay in surgery, tourniquet time, and Sanders classification. We conducted a retrospective cohort study in a teaching hospital from 2004 to 2011 evaluating a single surgeon series of calcaneal open reduction internal fixation via an extensile lateral approach. Patient demographics, mechanism of injury, history preexisting medical comorbidity, smoking status, soft tissue condition, delay in surgery, tourniquet time, presence of superficial or deep infection, and treatment of any infection were noted. Superficial and deep infection rate were 11.6% and 2.9%, respectively. Smokers had an increased rate of 12.5% and 6.25%, respectively. Most infections settled with antibiotics, and only 2 cases required surgical debridement. In conclusion, all the deep infections occurred in smokers whose surgery was delayed for more than 14 days. We found no increase in the rate of wound complications in association with age of patient, Sanders grading, or tourniquet time. Levels of Evidence: Prognostic Level III, retrospective comparative cohort study